2016
DOI: 10.1093/aje/kww177
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Collection Methods for Fecal Samples in Microbiome Studies

Abstract: Prospective cohort studies are needed to assess the relationship between the fecal microbiome and human health and disease. To evaluate fecal collection methods, we determined technical reproducibility, stability at ambient temperature, and accuracy of 5 fecal collection methods (no additive, 95% ethanol, RNAlater Stabilization Solution, fecal occult blood test cards, and fecal immunochemical test tubes). Fifty-two healthy volunteers provided fecal samples at the Mayo Clinic in Rochester, Minnesota, in 2014. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
125
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 123 publications
(133 citation statements)
references
References 36 publications
7
125
1
Order By: Relevance
“…In general, our findings agree with those from many of the previous studies considering the impact of the collection method and short-term storage at room temperature in predominantly Western populations (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). In general, FOBT cards or Whatman FTA cards, which have feces smeared on the card itself that then dries, have been found to be relatively stable at room temperature and similar to immediately frozen samples without preservatives (6,10,15,21,22).…”
Section: Figsupporting
confidence: 90%
See 4 more Smart Citations
“…In general, our findings agree with those from many of the previous studies considering the impact of the collection method and short-term storage at room temperature in predominantly Western populations (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). In general, FOBT cards or Whatman FTA cards, which have feces smeared on the card itself that then dries, have been found to be relatively stable at room temperature and similar to immediately frozen samples without preservatives (6,10,15,21,22).…”
Section: Figsupporting
confidence: 90%
“…Fecal samples stored in 95% ethanol (12,21) and RNAlater (6,11,12,15,19,22) appear to be adequately preserved in most studies, although some studies found some decreased diversity, DNA quality, or stability in samples stored in RNAlater (9,10,13,19,21). We and another group previously observed that FIT tubes, which store a small amount of feces from a probe in a buffer solution, stabilize fecal samples (22,23), but we were unable to replicate this finding in this study in Bangladesh.…”
Section: Figcontrasting
confidence: 61%
See 3 more Smart Citations